2003
DOI: 10.1021/jf025551i
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Anthocyanins and Their Aglycons

Abstract: The antioxidant activity of the six common anthocyanidins, pelargonidin, cyanidin, delphinidin, peonidin, petunidin, and malvidin, and their glycosidic forms was evaluated in three lipid-containing models [human low-density lipoprotein (LDL) and bulk and emulsified methyl linoleate]. In addition, the radical scavenging activity of the compounds against the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical was studied. Most anthocyanins and their aglycons acted as strong antioxidants in emulsion and LDL. Many compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

46
481
0
21

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 762 publications
(548 citation statements)
references
References 25 publications
46
481
0
21
Order By: Relevance
“…This is partly due to their anti-inflammatory properties (González-Gallego et al 2010;Landberg et al 2011;Rotelli et al 2003), antioxidant and free radical scavenging activities (García-Alonso et al 2009;Gray and DeWitt 1999;Kahkonen and Heinonen 2003;Matsumoto et al 2002;Tsuda et al 1994;Wang et al 1997), peroxidation inhibition (Tsuda et al 1996), and estrogenic/anti-estrogenic activity (Cassidy et al 2003). It has been largely proven that the beneficial potential of polyphenols as part of a healthy diet cannot be only explained by their antioxidant characteristics (Virgili and Marino 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to their anti-inflammatory properties (González-Gallego et al 2010;Landberg et al 2011;Rotelli et al 2003), antioxidant and free radical scavenging activities (García-Alonso et al 2009;Gray and DeWitt 1999;Kahkonen and Heinonen 2003;Matsumoto et al 2002;Tsuda et al 1994;Wang et al 1997), peroxidation inhibition (Tsuda et al 1996), and estrogenic/anti-estrogenic activity (Cassidy et al 2003). It has been largely proven that the beneficial potential of polyphenols as part of a healthy diet cannot be only explained by their antioxidant characteristics (Virgili and Marino 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among natural phenolic compounds, anthocyanins have shown scavenging activity against various artificially generated free radicals and the ability to prevent lipid oxidation (13,14). We have found that the berries of Phillyrea latifolia L., Pistacia lentiscus L., and Rubia peregrina L., three evergreen shrubs widely distributed in the Mediterranean area, are rich in anthocyanins (15).…”
Section: Introductionmentioning
confidence: 99%
“…Only six of the 16 anthocyanidins identified in natural products occur frequently and in many different vegetables and fruits: cyanidin, pelargonidin, delphinidin, peonidin, petunidin and malvidin (WU; PRIOR, 2005a;. Anthocyanins are highly studied compounds because of their effects on human health as antioxidant compounds, as shown in a number of in vitro and in vivo studies HEINONEN, 2003), for their anti-inflammatory effect modulating ciclooxygenase 1 and 2 enzymes (TALL et al, 2004) and their inhibitory effect on the development of some cancer cells (HAGIWARA; YOSHINO; ICHIBARA, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Only six of the 16 anthocyanidins identified in natural products occur frequently and in many different vegetables and fruits: cyanidin, pelargonidin, delphinidin, peonidin, petunidin and malvidin (WU; PRIOR, 2005a;. Anthocyanins are highly studied compounds because of their effects on human health as antioxidant compounds, as shown in a number of in vitro and in vivo studies HEINONEN, 2003), for their anti-inflammatory effect modulating ciclooxygenase 1 and 2 enzymes (TALL et al, 2004) and their inhibitory effect on the development of some cancer cells (HAGIWARA; YOSHINO; ICHIBARA, 2002).Among the small fruits group, including strawberry, raspberry, blueberry and blackberry crops, blackberry appears as the richest source of anthocyanins, with cyanidin content ranging from 93 to 280 mg.100 g -1 fresh weight depending on the cultivar (CONNOR et al, 2002), followed by black raspberry (up to 197 mg), blackberry (153 mg) and strawberry (32 mg) (WANG; LIN, 2000). Blackberry plants were introduced in Brazil by the Estação Experimental de Pelotas (RS), renamed…”
mentioning
confidence: 99%